The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0091415019864595
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Activities of Daily Living and Attitude Toward Own Aging Among the Elderly in China: A Chain Mediating Model

Abstract: This study used the 2014 China Longitudinal Aging Social Survey to explore the relationship between the activities of daily living, cognitive function, social support, and attitudes toward own aging, and a structural equation model was established to test the mediating effect. (a) Pearson correlations were performed between the total scores on each scale, and the activities of daily living were significantly negatively correlated with cognitive function and social support and significantly positively correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…The results of this study indicated that the elderly with IADLs decline were 4.635 times more likely to have cognitive impairment than those with independent IADLs. This finding was consistent with the results of previous studies, 11 , 36 which suggest that the decline of IADLs may be an indicator of potential cognitive impairment. Several studies 13 , 14 , 15 have confirmed that visual and hearing difficulties in seniors increase the risk of cognitive impairment, possibly because visual and hearing difficulties limit the ability of seniors to receive and process information and communicate; it is also because those with visual and hearing difficulties have difficulty remembering or recalling information as easily as normal individuals, and were therefore at increased risk for cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study indicated that the elderly with IADLs decline were 4.635 times more likely to have cognitive impairment than those with independent IADLs. This finding was consistent with the results of previous studies, 11 , 36 which suggest that the decline of IADLs may be an indicator of potential cognitive impairment. Several studies 13 , 14 , 15 have confirmed that visual and hearing difficulties in seniors increase the risk of cognitive impairment, possibly because visual and hearing difficulties limit the ability of seniors to receive and process information and communicate; it is also because those with visual and hearing difficulties have difficulty remembering or recalling information as easily as normal individuals, and were therefore at increased risk for cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
“…The higher attitude scores among urban older people resemble the findings of Hou et al [30]. Various environmental factors can affect perception of and attitudes towards the aging process, including education levels, economic status, and functional independence [31]- [33]. In this study, urban participants had higher education levels.…”
Section: Rural-urban Comparisonssupporting
confidence: 81%
“…It is well known that natural aging in the elderly is associated with cognitive decline, and many elderly people experience a gradual decline in cognitive function with age (22). In addition, the results of several previous studies in elderly patients over 65 years of age have shown that the ability of daily living is closely related to cognitive function (9,23,24), ADL score was negatively correlated with cognitive function score (25), whereas IADL is goal-oriented and includes more complex functional abilities such as cooking, handling nances, shopping, etc(26-28), good IADL is one of the reasons for good cognitive function (23), thinning of the medial temporal cortex caused by mild changes in IADL is associated with cognitive decline (29). It has also been shown that the changes in hippocampal volume or white matter in patients with cognitive impairment are independently related to the ability of daily life, which also implies the clinical value of the ADLs & IADLs (30).…”
Section: Discussionmentioning
confidence: 99%